2019
DOI: 10.1590/0104-9224/si24.18
|View full text |Cite
|
Sign up to set email alerts
|

Keyhole GTAW with Dynamic Wire Feeding Applied to Orbital Welding of 304L SS Pipes

Abstract: Currently, in the Brazilian Oil and Gas scenario the execution of welding processes for stainless steel consists mostly of manual applications, rendering hard any increase in productivity and repeatability. Therefore, the automation of this step allows several advances such as more reliable results, lower costs and healthier condition for welders. With the aim of developing automation for GTAW welding of these applications, experimental tests were carried out in a 304L stainless steel pipe laid out at 5G posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The capability of full penetration in a single pass, i.e., being able to perform single-pass welds without stopping, results in a shorter processing time as well as a lower susceptibility to welding failures. Although higher welding speeds (up to 8 mm/s) [16] have been reported in orbital GTAW when compared to FSW, the need for several filling passes makes the overall process slower. In this study, despite the reported defect-free welds of AISI 304 L stainless steel in pipes for the abovementioned travel speeds, no mechanical characterization was conducted.…”
Section: Advantages and Limitations Of Fsw Over Fusion Weldingmentioning
confidence: 99%
“…The capability of full penetration in a single pass, i.e., being able to perform single-pass welds without stopping, results in a shorter processing time as well as a lower susceptibility to welding failures. Although higher welding speeds (up to 8 mm/s) [16] have been reported in orbital GTAW when compared to FSW, the need for several filling passes makes the overall process slower. In this study, despite the reported defect-free welds of AISI 304 L stainless steel in pipes for the abovementioned travel speeds, no mechanical characterization was conducted.…”
Section: Advantages and Limitations Of Fsw Over Fusion Weldingmentioning
confidence: 99%
“…Moreover, increasing the welding speed to more than 6 mm/s gives rise to the formation of slag. In addition, Riffel et al [17] welded an SUS 304 L stainless steel pipe automatically at a speed of 500 mm/min under the monitor of high-dynamic-range videography. The welded joint was successfully formed without any porosity, discontinuities, or lack of fusion.…”
Section: Introductionmentioning
confidence: 99%